Association of adult hippocampal neurogenesis with alzheimer’s disease - Gope, Atryee (International Journal Of Community Medicine And Public Health, 2020)
Neurogenesis in the adult brain has been reported to occur within three distinct regions, of which Hippocampus is the most studied one because of its importance in cognition and memory. Alzheimer’s disease attributes to almost 62% of all dementia cases. A recent study has established a link between adult hippocampal neurogenesis and alzheimer’s disease wherein a sharp decline in AHN is observed in patients suffering from alzheimer’s. This review summarizes alzheimer’s disease, the decline in AHN in alzheimer’s patients and probes into the efficacy of the newly generated hippocampal neurons in the context of memory and cognition. It also discusses the potential of targeting reduced AHN in alzheimer’s patients using neural stem cell-based therapy.